11. CASE REPORT ON THE TREATMENT OF BENIGN ANASTOMOTIC STRICTURE AFTER ANTERIOR RESECTION FOR RECTAL CANCER USING ENDOSCOPIC METAL STENT PLACEMENT (Vietnam Journal of Community Medicine, 2024)
Objective: To present a case of benign anastomotic stricture following laparoscopic anterior resection for rectal cancer and discuss the endoscopic treatment method using a self-expanding metal stent (SEMS).Case presentation: A 74-year-old female patient, with a history of laparoscopic anterior resection for stage IIB rectal cancer, was later diagnosed with a colorectal anastomotic stricture. The patient was successfully treated with endoscopic placement of a self-expanding metal stent.Results: After stent placement, the patient was able to defecate normally without complications during or after the procedure. Radiographic and endoscopic imaging confirmed that the stent was correctly positioned and fully expanded. The patient was discharged on postoperative day 4 without any late complications. Initial long-term results showed no signs of recurrent stricture, and the stent remained in place.Conclusion: Self-expanding metal stent placement is a minimally invasive, safe, and effective method for treating colorectal anastomotic strictures. Careful patient selection is essential to ensure the efficacy of this approach.
Keywords: anastomotic stricture; rectal cancer; laparoscopic surgery; self-expanding metal stent